Implementation Fuzzy Mamdani Based Grading System for Laboratory Course in Politeknik Negeri Medan - Handasah, Ummu; Afdila, Ryandika; Yusdartono, Habib Muharry; Daulay, Muhammad Sukri Habibi (Bahasa Indonesia, 2023)
The traditional grading methods used for laboratory courses often fail to capture the nuances of student performance, overlooking the contributions of attendance, lab report quality, lab skills, midterm exams, and final exams. To address this shortcoming, this study introduces a novel grading approach that employs fuzzy logic, specifically the Fuzzy Mamdani technique, to produce more comprehensive and accurate final grades. Using a dataset comprising 26 students, our study demonstrates the effectiveness of the Fuzzy Mamdani approach in determining final grades, revealing a range from 20.01 to 87.98. The crisp output values produced highlight the adaptability and accuracy of the method in evaluating complex educational processes. By applying fuzzy logic to laboratory course grading, we bridge a significant research gap and contribute to a deeper understanding of how this technology can enhance educational assessments, particularly in specialized settings like laboratories. This study paves the way for more nuanced and equitable grading practices, ensuring that students receive grades that accurately reflect their overall performance.